Particulate Matter 2.5 and Hematological Disorders From Dust to Diseases: A Systematic Review of Available Evidence - Fongsodsri, Kamonpan; Chamnanchanunt, Supat; Desakorn, Varunee; Thanachartwet, Vipa; Sahassananda, Duangjai; Rojnuckarin, Ponlapat; Umemura, Tsukuru (Frontiers in Medicine, 2021)
Particulate matter2.5 (PM2.5) in the air enters the human body by diffusion into blood circulation. Therefore, hematological abnormalities might be occurred from this toxic particles, but few studies have been reported. According to Cochrane guidance, we performed a systematic review on the relationship between PM2.5 exposure and the risk of hematological disorders. Ten articles were included in this review. Anemia was found among children and elderly populations with 2-5-year-PM2.5-exposure. Young children from the mothers who exposed to air pollution during pregnancy had a higher incidence of leukemia similar to elderly. Supporting this data, outdoor workers also showed abnormal epigenetic modifications after exposure to very high PM2.5 levels. Adults living in high PM2.5 areas for 2-years were more likely to develop thrombocytosis. Finally, elderly populations with 7-8-year-PM2.5-exposure showed increased risks of venous thromboembolism. In conclusion, the associations between PM2.5 and hematological aberrations among high-risk people with long term-exposure were reported.